Menyusuri kota jejak kejayaan Islam - Ruslan, Heri. (Jakarta : Harian Republika, 2011)
Islamic civilization in cities in the world.
Keywords: Islamic civilization; Islamic countries; Islamic countries -- Civilization; Islamic Empire -- History